Optimising casting film Parameters for LPDE material assessment - Nur Qurratul Ain, Adanan; Faiz, Mohd Turan; Kartina, Johan; Anis Izzati, Md Yusoff; Hui Xin, Wong (Springer, Singapore, 2022)
The growing demand for disposable gloves, especially from the healthcare industry amidst the ongoing Covid-19 pandemic and rising awareness about Healthcare-Associated Infections (HAIs). One of the ways to produce disposable gloves is using cast LDPE film machine. The quality of the products depends on material resin used, machine casting film design, part design and the selection of process parameters. However, the part design and casting film design are done at the initial stage of product development, it cannot be change easily. To manufacture a better quality of cast LDPE gloves, the best LDPE casting film parameters have to be identified. This research aims to identify the best LDPE casting film parameters in producing disposable gloves in terms of strong sealed but edges failed defect rate in production line. The three LDPE casting film parameters such as tensile strength, melt flow index (MFI) and load weight of resin were chosen to study their effect on the defect rate. In this research, the Taguchi method is used to optimize the best process parameters. On the other hand, an orthogonal array (OA), signal-to-noise (S/N) ratio, and ANOVA were employed to investigate the strong sealed but edges failed defect rate. According to the results obtained, the tensile strength of 34 MPa, melt flow index of 3 g/10 min and load weight of 2 kg were found to be the best combination of LDPE casting film parameters to fabricate the better performance of LDPE disposable gloves which give the lowest strong sealed but edges failed defect rate with 2%. Based on the statistical ANOVA analysis results, the most significant parameter affecting the strong sealed but edges failed defect rate of LDPE disposable gloves is tensile strength, which is indicated by the percentage contribution of P =55.56%, followed by melt flow index with 38.89%. The load weight of LDPE resin is the least significant parameter with 5.55%. To conclude, Taguchi and ANOVA method show that tensile strength is the most significant parameter to get the least strong sealed but edges failed defect rate.